STUDYING THE BIOPHARMACEUTICAL PROPERTIES OF THE DRUG “BISKOR” BY METHODS IN VITRO AND IN VIVO - Mannanovna, Yunusova Kholida; qizi, Jaloliddinova Muattar Shukhrat; Bakhtiyarovna, Ilkhamova Nargiza; qizi, Anvarova Farangiz Jamshid (International Journal of Membrane Science and Technology, 2023)
The results of the study of the biopharmaceutical properties of the recommended tablets “Biskor” by methods in vitro and in vivo. The first step in a bioavailability study is to determine the solubility or release time of the drug from the dosage form. It has been established that the solubility test in the first approximation characterizes the bioavailability of the drug, since in practice there is a very frequent correlation between the rate of dissolution and absorption. The solubility, foreign impurities and the quantitative content of active substances were studied.